2021
DOI: 10.47836/ifrj.28.5.05
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different compositions of starter cultures developed from phytic acid-degrading lactic acid bacteria on the sensory quality of bread

Abstract: Sourdough is an initial product used in cereal fermentation, usually prepared by adding lactic acid bacteria (LAB) strains to a mixture of wheat and water. Phytic acid present in wheat flours negatively affects the bioavailability of bread. LAB is found to have phytase activity. The present work thus aimed to determine the effect of starter culture combinations developed from phytic acid-degrading LAB (PAD-LAB) strains isolated from sourdough samples on bread sensory quality. De Man, Rogosa, and Sharpe (MRS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
1
2
1
Order By: Relevance
“…The pH of breads was closely similar to the finding of Dogan (2021), who reported that the pH of breads was 5.19. The titratable acidity (TA) of the breads was higher than the finding of Dashen et al .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The pH of breads was closely similar to the finding of Dogan (2021), who reported that the pH of breads was 5.19. The titratable acidity (TA) of the breads was higher than the finding of Dashen et al .…”
Section: Resultssupporting
confidence: 88%
“…In the current study, at 0 day storage, the overall mean scores of colour was 7.4, texture 7.6, taste 7.3, odour 7.8, and overall acceptability 7.5 (Table 4). This outcome was better than that of Dogan (2021), who reported that breads' average scores for colour, texture, odour, taste, and overall acceptability were 4.0, 3.7, 3.8, 3.7, and 3.9, respectively. In contrast, Stavros et al .…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…Endogenous phytase is missing in humans and, therefore, exogenous enzymatic supplementation can be considered as an efficient alternative to overcome this lack [52] . Considering that LAB [53] and non-LAB [54] have shown the ability to decrease phytic acid levels in sourdough, both cereals and pseudo-cereals can be fermented by microbes to achieve the same outcome [55] or, as in our case, the supplementation can be provided by gut colonizing probiotics selected by high phytase activity.…”
Section: Discussionmentioning
confidence: 92%